Spatiotemporal variability in the South American mammalian fossil record and its impact on macroevolutionary inference - Pedro D. de S. Ugarte; João C. S. Nascimento; Mathias M. Pires (Frontiers in Mammal Science)
Macroevolutionary studies using the fossil record have provided valuable information about the evolutionary history of mammals, helping us to understand some of the processes underlying shifts in diversification dynamics. Yet, most studies on mammal diversification have focused on the Northern Hemisphere. The general view that the quality of the fossil record of South American clades is too limited has precluded continental-level macroevolutionary studies in the continent. However, to adequately evaluate how much we can learn from the South American fossil record, we need to understand how the limitations of the fossil record affect the uncertainty of macroevolutionary estimates. Here, we investigated the spatiotemporal distribution of fossil occurrences from eleven South American mammalian clades and used a Bayesian approach that accounts for the incompleteness of the fossil record to analyze how estimates of times of origination and extinction, and origination and extinction rates are affected by the quality of the fossil record. We show that the main shortcoming of the South American mammalian fossil record is not its overall quality but its spatiotemporal unevenness. Most early South American and early immigrant clades have lower preservation rates than late immigrant clades. Accordingly, uncertainty in root age and estimates of times of origination and extinction is larger for earlier South American clades. Despite the limitations of the fossil record, we were still able to identify significant rate shifts throughout the diversification of most South American clades that may be explained by environmental changes. Yet, we also find discrepancies with macroevolutionary patterns inferred from phylogenies, which suggest that some of the patterns we detect with fossils might reflect regional macroevolutionary trends or be driven by lineages with higher preservation. Contrasting the results obtained using different approaches, such as rate estimates from fossils and molecular data, to find where they converge and diverge, may help to delineate the spatial scale and phylogenetic scope of observed macroevolutionary patterns. Our work contributes to a better understanding of the limitations and opportunities in the research about the evolution of South American mammals